2017
DOI: 10.3389/fendo.2017.00089
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Pulsatile Interleukin-6 As a Treatment Option for Diabetic Peripheral Neuropathy

Abstract: Diabetic peripheral neuropathy (DPN) remains one of the most common and serious complications of diabetes. Currently, pharmacological agents are limited to treating the pain associated with DPN, and do not address the underlying pathological mechanisms driving nerve damage, thus leaving a significant unmet medical need. Interestingly, research conducted using exercise as a treatment for DPN has revealed interleukin-6 (IL-6) signaling to be associated with many positive benefits such as enhanced blood flow and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 103 publications
0
22
0
2
Order By: Relevance
“…The inflammatory response is likely critical for the development and progression of DPN, despite the existence of various other acceptable pathogenetic factors, which may explain the nerve damage observed in DPN rats. 17 In recent years, studies have shown that TNF-α is closely related to DPN and is upregulated in the sciatic nerve of DPN rats. 18 The upregulation of TNF-α promotes a series of downstream inflammatory responses, which leads to damage and demyelination of the nerve cells, resulting in the final peripheral nerve dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response is likely critical for the development and progression of DPN, despite the existence of various other acceptable pathogenetic factors, which may explain the nerve damage observed in DPN rats. 17 In recent years, studies have shown that TNF-α is closely related to DPN and is upregulated in the sciatic nerve of DPN rats. 18 The upregulation of TNF-α promotes a series of downstream inflammatory responses, which leads to damage and demyelination of the nerve cells, resulting in the final peripheral nerve dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The observed association between serum IL6 concentrations and ADSCs proliferation is consistent with previous studies highlighting the importance of IL6 in the maintenance and growth of mesenchymal stem cells (Pricola et al, 2009; van de Vyver et al, 2016). The mechanism of which is most likely related to the pleiotropic effects of IL6 capable of eliciting both a pro- and anti-inflammatory response depending on the environmental context (Cox et al, 2017). Classical IL6 signaling is mediated through the association of the protein-bound receptor complex (IL6 + IL6R) with the gp130 receptor subunit and elicits an anti-inflammatory protective effect (Rose-John, 2012, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of biological therapy with low doses of IL-6 has been demonstrated to promote improvement of blood flow, decrease chronic inflammation, and regenerate peripheral nerve fibers. Accordingly, IL-6 may prove to be an effective treatment for the protection and/or restoration of peripheral nerve function in DPN [50]; see Table 1.…”
Section: Treatments For Diabetic Foot Ulcersmentioning
confidence: 99%